Finite strain has no influence on the illite crystallinity of tectonized Eocene limestone breccias of the Morcles nappe, Swiss Alps - Burkhard, Martin; Badertscher, Nicolas P. (My University, 2001)
The relationship between illite crystallinity (IC) and finite strain as well as lattice strain and crystallite size of illite is examined in a series of 27 deformed breccia samples from the inverted limb of the Morcles nappe. The IC is determined independently for limestone components and a red/green clay-silt matrix. The finite strain varies widely (D = 0.8ÿ2.5). The IC values vary from diagenetic to epizonal, but no correlation with finite strain could be established. The spread of IC values is explained by heterogeneities within the protolith which have not been homogenized/ obliterated by the anchi- to epizonal metamorphic overprint. While limestone pebbles display IC values in agreement with the regional metamorphic conditions, the clay-silt matrix has anomalously high IC values, even after deconvolution of the 10 A Ê peak to correct for the presence of paragonite/ muscovite. No correlation could be established between finite strain, lattice strain and/or crystallite size of illite.